Analisis Pengaruh Variabel-variabel Ekonomi Makro terhadap Return Saham - Sunaryo Sunaryo (Binus Business Review, 2013)
The primary objective of this research is to learn the effecting inflation, interest rate of Indonesian bank certificate, changes of exchange rate, and changes of outstanding money amounts variables with changes of the return Jakarta composite index. Secondary data were collected from Jakarta composite Index, annual Indonesian bank report, Jakarta daily newspaper, and preceding research by using judgment sampling until it got normal distribution data with Kolmogorov-Smirnov test. The results of this research described that inflation, Interest Rate of Indonesian Bank Certificate, and changes of outstanding money variables have not significant effect to the changes of return Jakarta composite index; and changes of exchange rate have significant effect to the changes return of Jakarta composite index. Inflation, interest rate of Indonesian bank certificate, changes of exchange rate, and changes of outstanding money amounts variables have simultaneous significant effect to thechanges return of Jakarta composite index. Topic of this research may continue using other countries or added more than 75.20 % of independence variables.